Biodiesel production from Scenedesmus bijuga grown in anaerobically digested food wastewater effluent. (May 2015) - Shin, Dong Yun; Cho, Hyun Uk; Utomo, Joseph Christian; Choi, Yun-Nam; Xu, Xu; Park, Jong Moon
Highlights: Anaerobically digested food wastewater effluent was used for algal cultivation. Biodiesel was produced by Scenedesmus bijuga . Different dilution ratios were compared with lipid productivity. Nutrient removal was analyzed in cultivation. Quality of FAMEs was evaluated by two indicators. Abstract: Microalgae, Scenedesmus bijuga, was cultivated in anaerobically digested food wastewater effluent (FWE) to treat the wastewater and produce biodiesel simultaneously. Three different mixing ratios with municipal wastewater were compared for finding out proper dilution ratio in biodiesel production. Of these, 1/20 diluted FWE showed the highest biomass production (1.49 g/L). Lipid content was highest in 1/10 diluted FWE (35.06%), and the lipid productivity showed maximum value in 1/20 diluted FWE (15.59 mg/L/d). Nutrient removal was also measured in the cultivation. FAME compositions were mainly composed of C16–C18 (Over 98.94%) in S. bijuga . In addition, quality of FAMEs was evaluated by Cetane Number (CN) and Bis-allylic Position Equivalent (BAPE).